The Application of Teaching Students’ Speaking Skill through Role Play (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
This study focuses on improving speaking skills using role playing techniques. Speaking is the skill of conveying messages through spoken language. The link between messages and spoken language as a medium of delivery is very heavy. The message received by the listener is not in the original form, but in another form, namely the sound of language.  The listener then tries to divert the message in the form of the sound of the language into its original form.  The sample was students of the tenth-grade of SMA Negeri 1 Kragan Rembang with a total of 36 students.  Instrument of the research was speaking test.  The researchers conducted pre-test and post-test sessions.  Data collection was done by using quantitative methods.  Based on data analysis from the experimental group showed that the mean of pre-test was 338.75 while post-test was 353.64. In the T-test showed that the sig. (1-tailed) of experiment 2.045>2.756 It means that there is a significance difference in the result of students' learning scores. The result of this research showed that role play technique can improve students’ speaking skill. role play technique is a good and easy technique to help develop and organize ideas in speaking.
Keywords: speaking skill and role play technique